Relationship of chronic kidney disease of the with glycemic status, cardiovascular diseases and laboratory indicators in patients with type 2 diabetes mellitus - S. Kh. Mehdiyev; I. I. Mustafaev; M. N. Mamedov (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the relationship of chronic kidney disease parameters with glycemic control, subclinical and clinical signs of cardiovascular diseases and laboratory parameters.Material and methods. The study included 528 patients with type 2 diabetes mellitus (T2DM) aged 30-69 years. All respondents answered questions from the ARIC questionnaire about T2DM and cardiovascular diseases. We determined the ankle-brachial index, sonographic left ventricular hypertrophy, intima-media thickness and defined hypertensive, diabetic angiopathy and polyneuropathy. The levels of glycemia, lipid spectrum, creatinine, uric acid, glycohemoglobin were evaluted. Glomerular filtration rate (GFR) was calculated using the Cockroft-Gault method, and microalbuminuria (MAU) was determined using Micral tests.Results. Glycohemoglobin did not depend on MAU (p=0,564), a decrease in GFR was accompanied by an improvement in glycemic control (p=0,393). There was a direct association between MAU and the duration of diabetes (p=0,001), in patients with a longer course of the disease GFR was reduced (p=0,001). With increasing of systolic blood pressure, MAU progressed (p=0,016), while GFR decreased (p<0,01). In patients with hypertensive angiopathy, MAU of 100 mg/dl (p=0,001) and stage 2 of chronic kidney disease (p=0,048) occurred with the highest incidence (1/4) (p=0,048). According to the survey, angina was found in patients with MAU of 100 mg/dl (p=0,006). Chronic heart failure led to the progression of albuminuria (p=0,007), in patients with clinical signs of atherosclerosis of the lower extremities, the frequency of MAU was 72-87,5% (p=0,032). The highest intima-media thickness of the right carotid artery in patients with GFR 89-60 ml/min and MAU 100 mg/dL (respectively, 1,77±0,41, 1,33±0,49) were determined. Sonographic signs of left ventricular hypertrophy were observed in 84,6% of patients with an MAU of 300 mg/dL (p=0,022), as the severity of albuminuria increased, the ejection fraction of the left ventricle decreased (p=0,003). Albuminuria increased the level of myocardial remodeling (p<0,05) and this indicator showed a direct relationship with the severity of MAU. With an increase in albuminuria, the degree of triglyceridemia increased. An increase of MAU level and a decrease in GFR was accompanied by an increase in creatininemia (p<0,001). A direct relationship was found between lithemia and MAU. Conversely, a decrease in GFR contributed to the progression of MAU (p<0,001).Conclusion. Reduction of GFR and MAU are the major risk factors for cardiovascular diseases in the Azerbaijani population with T2DM. We suppose that periodic monitoring of these parameters for primary and secondary prevention of diabetic nephropathy plays an important role.